Blistering and hydrogen retention in poly- and single- crystals of aluminum by a joint experimental-modeling approach. (August 2019) - Quiros, C.; Mougenot, J.; Bisson, R.; Redolfi, M.; Michau, A.; Hassouni, K.; Lombardi, G.
Highlights: Use of Aluminum as a proxy for Beryllium. Studies by experiments and modeling of hydrogen trapping in blisters. Role of the boundaries in hydrogen trapping studied by comparing single-crystals and poly-crystals. Abstract: Aluminum samples have been exposed to a hydrogen plasma generated by a low-pressure – high-density microwave reactor. Aluminum has been chosen as a surrogate for Beryllium. The fluence was kept below 4 × 10 24 ions/m 2, in order to study the first steps of nucleation and growth of surface and bulk defects, i.e. blisters and bubbles. Experimental analyzes and macroscopic rate equation (MRE) modeling on poly- and single- crystals were made to investigate the role played by grains boundaries in the hydrogen retention. Temperature programmed desorption (TPD) on Al poly-crystals revealed the production of aluminum hydrides (alanes) as majority species in the desorption flux. Comparison of microscopy observations for three different single-crystal orientations (〈100〉, 〈110〉 and 〈111〉) allowed to determine preferential orientations able to attenuate the formation of blisters.